Efforts to Improve Student Learning Outcomes in Islamic Education Learning through the Sharing Model and Audio Visual Media at SMP Negeri 1 Pulau Banyak Barat - Hutagalung, Nofi Pofiana; Ahmad, Nurmi (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve student learning outcomes in Islamic Education subjects through the application of a sharing-based learning model and the use of audio-visual media at SMP Negeri 1 Pulau Banyak Barat. This study uses a classroom action research (CAR) approach which is implemented in two cycles. Each cycle consists of planning, implementation, observation, and reflection. Data were collected through observation, interviews, and learning outcome tests given at the beginning and end of each cycle. The results of the study indicate that the application of a sharing-based learning model can increase student involvement and active participation in the learning process. Students are more active in discussing and sharing ideas with their friends, so that their understanding of Islamic Education materials becomes deeper. In addition, the use of audio-visual media such as videos and images that are relevant to the subject matter, helps students understand concepts that are more abstract and difficult to explain verbally. In the first cycle, although there was an increase in student participation and understanding, several challenges were found such as the lack of focus on group discussions and distractions from the media used. In the second cycle, improvements were made by providing clearer instructions and limiting the time spent using media, which resulted in a significant increase in student involvement and understanding of the material. Overall, the implementation of sharing-based learning models and the use of audio-visual media have proven effective in improving student learning outcomes in Islamic Education subjects at SMP Negeri 1 Pulau Banyak Barat. This study provides an overview that the use of interactive learning methods and interesting media can improve the quality of learning and student involvement in the learning process.